Islam and the Challenge of Human Rights: By Abdulaziz Sachedina (City: Oxford University Press, 2009. 249 pages.) (American Journal of Islam and Society, 2010)
In Islam and the Challenge of Human Rights, Abdulaziz Sachedina calls fora new conversation between religious and secular forces to achieve an “overlappingconsensus” on human rights and its underlying principles. Accordingto him, developing a firm foundation for human rights in Islam is key toreaching such a consensus. Thus after critiquing the contemporary humanrights regime and the traditionalist Muslim approach to it, he tries to developsuch a theological foundation. Although showing a keen awareness of thenumerous tensions between the international human rights framework andthe Muslim world’s cultural, social, and political sensibilities, the authorposits that some form of notions of individuality, human agency, and humandignity are compatible with the Islamic revelation. Recognizing this providesIslam and the human rights project important “common moral terrain.” ...